A Literature Review of Psychosocial Comorbidities Related to Working Capacity After Aneurysmal Subarachnoid Hemorrhage. Issue 3 (June 2017) - Turi, Eleanor; Conley, Yvette; Stanfill, Ansley Grimes
Abstract : ABSTRACT: Objective: The aim of this study was to describe literature regarding the impact of psychosocial comorbidities on working capacity after aneurysmal subarachnoid hemorrhage (aSAH).Design/Methods: This study is a review of the literature using PubMed, CINAHL, PyschINFO, and Google Scholar.Results: Patients with aSAH affected by depression, anxiety, cognitive impairment, or posttraumatic stress disorder are less likely to return to work, although there are mixed results. These may be due to inconsistent inclusion, adjustment of demographic and clinical variables shown to be associated with return to work, and differences in instrumentation and sample size.Conclusions: Working capacity after aSAH is likely affected by poor psychosocial outcomes, but future research should consider the standardization of demographic and clinical data, use standardized measurement tools, and consider the interrelatedness between psychosocial comorbidities.